COMPARATIVE STUDY BETWEEN GROUP PILE OUNDATION DESIGN AND RAFT FOUNDATION WITH BORED PILE SETTLEMENT REDUCER AT OFFICE BUILDING IN JAKARTA - NURANI SJAFRUDDIN (NIM: 15011115), ASRI
Group pile foundation and raft foundation with bored pile settlement reducer are widely-used foundation system at most of high building constructions in Indonesia. Physically, both of them do not have significant difference, except for their load transfer mechanism. At the group pile foundation design, only the bearing capacity of the pile foundations is considered, the pile cap is only considered as restrainer. At the raft foundation with bored pile settlement reducer, the pile cap also acts as a raft foundation of which bearing capacity is calculated on load transfer mechanism from the upper structure to the ground. The result of this study shows the comparison of design which is needed to support the structure between group pile foundation design and raft foundation with bored pile settlement reducer. It is a design which meets determined requirements in upholding load; including pile diameter, pile length, number of piles, space between piles, and raft dimension. The design will be further analized with LPile and GROUP program to obtain results, in the form of axial force, deflection, shear force, and moment force in the pile. The settlement analysis and safety factor are calculated by using PLAXIS 2D program. Besides, load proportion received by pile foundation and raft foundation are calculated with PLAXIS 3D program. Design reinforcement,which is needed for pile foundation and raft foundation, is conducted as well.